Berberis aristata, Elaeis guineensis and Coffea canephora Extracts Modulate the Insulin Receptor Expression and Improve Hepatic Steatosis in NAFLD Patients: A Pilot Clinical Trial - Cossiga, Valentina (Nutrients, 2019)
Non-alcoholic fatty liver disease (NAFLD) is associated with insulin resistance and diabetes. A reduction in insulin receptor (IR) expression has been reported in these patients. The aims of this study were to evaluate the effects of a mixture of plant extracts consisting of Berberis aristata, Elaeis guineensis and decaffeinated green coffee by Coffea canephora on the improvement of glycaemic profile, through the modulation of IR levels, and of hepatic steatosis in NAFLD patients. Forty-nine patients with a grade of steatosis S1-S2 were randomly allocated to the treatment with plant extracts or placebo for six months. Hepatic steatosis was evaluated using transient elastography with CAP (controlled attenuation parameter). Glucose, insulin, and IR levels were measured in serum samples. At the end of the study, patients treated with plant extracts displayed a significant reduction of serum glucose (p < 0.001), insulin levels (p < 0.01), homeostatic model assessment for insulin resistance (HOMA-IR) index (p < 0.001), and CAP value (p < 0.01) compared to placebo. Moreover, the IR expression was increased significantly in the plant extracts group compared to the placebo group (p < 0.05). The combination of plant extracts increases serum IR levels, determining amelioration of glycemic profile and improvement of hepatic steatosis in NAFLD patients.